Validity and Reliability Study of Listening Attitude Scale for Prospective Teachers - Kadir Kaplan (International Journal of Contemporary Educational Research, 2023)
The aim of this study is to develop a measurement tool to measure the listening/watching attitudes of pre-service teachers. 387 pre-service teachers were administered the scale, and its validity and reliability studies were conducted by exploratory factor analysis, internal consistency measurement, and confirmatory factor analysis. EFA revealed that the scale has four dimensions. To determine the reliability of the scale, the Cronbach Alpha internal consistency coefficient was calculated at 0.928. In the principal component analysis, Kaiser-Meyer-Olkin (KMO) coefficient was found to be 0.937. In addition, the Barlett Sphericity test was significant (χ2 = 4607.552; p<0.05). Varimax rotation resulted in factor loadings ranging between 0.37 and 0.91. In CFA, the standardized regression coefficients averaged around 0.700  and the items in each dimension had a significant predictive power. As a result of the analysis, a valid and reliable scale was obtained.